Kualifikasi Da’i dalam Perspektif Tafsir al-Maraghi dan Relevansinya dengan Kondisi di Indonesia - Zumrodi Zumrodi (AL-BURHAN, 2022)
Islam is a religion that contains the values of mercy and peace. However, these values will not be realized without being socialized and preached. To be able to preach all of this requires a qualified da'i. This study aims to explore Al-Maraghi's assesment in the book "Tafsir Al-Qur'an Al-Karim" about qualifications and their relevance to conditions in Indonesia. The type of this research is library research with descriptive qualitative method. While the analyst used is a content analysis. The data sources include primary data sources and secondary data sources. The primary data source is the book "Tafsir Al-Qur'an Al-Karim", and the secondary data sources in the form of books of interpretation, journals, and books related to research. As for the findings: first, a preacher must understand the Quran. Second, a Da'i must understand the sunnah of the prophet. Third, a Da'i must understand the history of khulafa'rrasyidin. Fourth, a Da'i must understand the various sects or schools of thought that exist in society. Fifth, a Da'i must know the language, customs, traditions and culture that exist in the community. Sixth, this qualification is very relevant to the conditions in Indonesia as a plural or majmu' country.